In the aftermath of disclosing child sexual abuse: consequences, needs, and wishes. Issue 3 (2nd September 2017) - Stiller, Anja; Hellmann, Deborah F.
ABSTRACT: Experiencing child sexual abuse (CSA) can have enormous consequences for the victims. However, reporting rates are comparably low. Thus, it is essential to consider the wishes and needs of disclosing CSA victims in order to develop measures that can improve the disclosure and reporting of CSA. We analysed data of a subsample of n = 394 victims of contact CSA from a representative victim survey ( N = 11, 428) conducted by the Criminological Research Institute of Lower Saxony, Germany, in 2011. Overall, 76% of the victims disclosed their CSA experience to somebody. However, only 14% of the cases were made known to law enforcement agencies. Of the disclosing victims, only one-third was believed and 43% reported that the disclosure led to no further consequences. Overall, being believed as well as supported by the victims' family proved to be crucial. Implications are discussed against the background of previous research.